COMPARISON STUDY ON TEACHER MOTIVATION AT TAMAN PEMBACAAN ALQURAN (TPQ) - Reza Fahmi (Islam Realitas: Journal of Islamic and Social Studies, 2017)
The research was based on the fact that the TPQ teachers should receive incentives differently depend on their motivation. When the teachers receive high incentives, they also should have high motivation to work compared to those who receive lower incentives. TPQ teachers can raise the motivation in teaching and encouraging the action towards a certain goal after getting encouragement in the form of incentive or certification. The purpose of this study is to describe the work motivation on TPQ teacher, TPQ teacher’s certification, then to test whether any discrepancy of motivation between those who receive incentives with B and C certificate in the Village Kuranji, Kuranji District of Padang. This study uses a quantitative method with data analysis techniques by using two-independent-samples test which was processed with SPSS version 24.0 for Windows. Variables use in this research is the work motivation. The population in this study is TPQ teachers who are located in the Village Kuranji, Kuranji District of the city of Padang who is 93 people and sample around 38 people. The sampling study uses simple random sampling. The data obtained by using psychological scale, which is based on the Likert scale model; this study uses a scale as a measurement that is work motivation, and has a reliability of 0.740. Based on the results of data analysis, it shows that the Independent Sample T-Test with tcount> t table (0.688> 0.05) then the hypothesis Ho accepted, which is meant there is no discrepancy in work motivation among teachers who receive B certification with those who receive C certification in Kuranji District Padang. Penelitian ini didasarkan fakta bahwa seharusnya guru TPQ yang menerima insentif dengan jumlah yang berbeda memiliki motivasi kerja yang berbeda. Ketika guru yang menerima insentif dengan jumlah yang lebih banyak seharusnya memiliki motivasi kerja yang lebih tinggi dibandingkan guru yang menerima insentif yang lebih rendah. Dimana guru TPQ dapat meningkatkan motivasi kerja dalam mengajar dan mendorong perbuatan ke arah suatu tujuan tertentu setelah mendapat dorongan berupa insentif atau sertifikasi guru TPQ yang diterima. Tujuan dari penelitian ini adalah untuk menjelaskan tentang motivasi kerja pada guru TPQ, sertifikasi guru TPQ, kemudian untuk menguji apakah ada atau tidaknya perbedaan motivasi kerja guru TPQ antara yang menerima insentif dengan sertifikasi B dan C di Kelurahan Kuranji Kecamatan Kuranji Kota Padang. Penelitian ini menggunakan metode kuantitatif dengan teknik analisis data yaitu analisis uji dua sampel independen (Two-Independent-Samples Test) yang diolah dengan program SPSS versi 24.0 for windows. Variabel yang digunakan dalam penelitian ini adalah motivasi kerja. Populasi dalam penelitian ini adalah guru TPQ yang berada di Kelurahan Kuranji Kecamatan Kuranji Kota Padang yang berjumlah 93 orang dan sampel penelitian berjumlah 38 orang. Penarikan sampel penelitian dengan menggunakansimple random sampling. Data diperoleh dengan menggunakan skala psikologi, yang berpedoman pada skala model Likert, penelitian ini menggunakan satu buah skala sebagai alat ukur yaitu skala motivasi kerja, dan memiliki reliabilitas 0,740. Bedasarkan hasil analisis data penelitian menunjukan Independent Sample T-Test denganthitung> ttabel (0,688>0,05) maka hipotesis Ho diterima artinya tidak ada perbedaan motivasi kerja antara guru yang menerima sertifikasi B denga guru yang menerima sertfikasi C di Kelurahan Kuranji Kecamatan Kuranji Kota Padang.